The titans sustainability and industry 4.0 working for the planet earth - Reis, José Salvador da Motta (2023)
The history of industry is marked by revolutions, the Fourth Industrial Revolution provides opportunities for sustainability, and means to reduce environmental degradation and social inclusion. This article aims to identify which factors impact the sustainability of an organization. The exploratory research was carried out by means of literature review and bibliographic research to achieve the objective of conducting a bibliometric study, identifying the evolution of publications, and the authors that make up this field of knowledge. It is necessary for companies and industries to be introduced to the global changes that Industry 4.0 has introduced in the manufacturing environment, making it possible to develop sustainable processes and products.